Projecting the Potential Budget Impact Analysis of Paliperidone Palmitate in Egyptian Adult Patients with Schizophrenia - Gihan Elsisi; Mohamed Ezzat; Mohamed Ramadan (Journal of Health Economics and Outcomes Research)
**Background:** Schizophrenia is a serious mental disorder that has greater negative consequences on role functioning than many other severe chronic diseases.